Mindfulness Meditation for Enhanced Mental Health and Academic Performance: A Review - Kathayat, Chetan Bahadur (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2024)
Purpose: This review aims to explore the effectiveness of mindfulness meditation in promoting mental health and improving academic performance among students. Methods: Studies examining the impact of mindfulness meditation on students' mental well-being and academic outcomes were reviewed and analyzed. Various aspects such as memory, focus, concentration, and overall academic performance were considered. Results: The findings suggest that mindfulness meditation holds significant benefits for students, including improved memory, enhanced focus and concentration, and ultimately, better academic performance. This practice also shows promise in reducing anxiety, stress, and depression among students. Value: This review contributes to understanding the potential of mindfulness meditation as a valuable tool for supporting students' mental health and academic success. It underscores the importance of integrating mindfulness practices into educational settings to foster holistic well-being. DOI: https://doi.org/10.69476/sdpr.2024.v01i01.003